Pengembangan Modul Tari Berbasis Digital untuk Meningkatkan Kompetensi Guru Sekolah Menengah Tari - Eko Purnomo; Trianti Nugraheni (Gondang: Jurnal Seni dan Budaya, 2019)
This study aimed to develop teacher modules to improve teachers' ability in managing learning materials. The study used a research and development method developed by Borg and Gall. The Subjects of the research was Teachers of Arts studies that are not backgrounded in art education. The data collection techniques used questionnaires and Focus Group Discussion. Technique of the data analysis used analisys description. Arts Subject is still guided by teachers who have no background in art education. On the other hand, the progress of information technology is still not utilized optimally. Art dance material in practice is easier to use audio visual media. Therefore, it is necessary to develop a digital-based module that can be accessed through various social media. The results showed a digital-based module developed to improve the ability of teachers in managing learning materials. Based on the research results, it can be concluded that the development of digital dance teacher module is used to improve the teachers’ competency of art and culture. Recommended, teachers are be able to develop modules in accordance with the needs in the field.